ENT300 Titan Futsal Centre / Mohd Husaini Mohd Yusoff...[et.al] - Mohd Husaini, Mohd Yusoff; Md. Kasim, Mohd Fahmi; Norman, Mahathir; Mohd Tarmizi, Luqman Hakim; Kameri, Hafriz (2009)
Company shareholders had unanimously agreed to name our company as TITAN. First, it shows our spirit in doing this business as a spirit of a titan. Also, we hope that by this name, Malaysian can recognize us and feel very proud of us. So that we will become their idol and we hope we can bring our business not only in Malaysia but also to the other country at higher level. Nature of Business We decided to apply partnership orientation in establishing TITAN, We choose this method because the company is going to be much secure in terms of financial and monetary. It is much easier to seek financial assistance to financial institutions for partnership business compare to the sole proprietorship. Besides, additional capital can be earned by recruiting additional shareholders. In addition, partnership orientation business is very easy to form with minimum formalities. Various ideas on how to improve the business and make it function efficiently can also be generated from numbers of shareholders.